Overview of distinct 8-oxoguanine profiles of messenger RNA in normal and senescent cancer cells - Huang, Jingwen; Lin, Yu; Zhao, Yingying; Wei, Lingbo (Frontiers in Cell and Developmental Biology, 2025)
BackgroundCellular senescence plays a key role in the development of cancer, but the underlying mechanisms are unknown. Recently, several recent studies have shown that RNA methylation is closely related to cancer cell aging. 8-Oxoguanine (o8G) is an important and widely distributed methylation modification whose role in cancer cell senescence is far from elucidated.MethodsIn this study, senescent cancer cell models (CaCO2 cells) were constructed by knocking down the ADAR1 gene. RNA immunoprecipitation sequencing was used to identify the o8G peaks on messenger RNA (mRNA) of normal CaCO2 cells and senescent CaCO2 cells, and the distribution characteristics of mRNA o8G modification were identified. Further bioinformatics analysis of the sequencing data was performed to preliminarily elucidate the potential function of the o8G-modified mRNA.ResultsThere were significant differences in mRNA o8G modification distribution between normal and senescent CaCO2 cells. It is suggested that o8G modification may play a key role in inducing cancer cells or promoting cancer cell senescence. Gene ontology (GO) enrichment analysis showed that the mRNAs modified by o8G were enriched in Cellular component organization or biogenesis, Focal adhesion, and RNA binding. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the genes modified by o8G are concentrated in Focal adhesion signaling pathway, Small cell lung cancer signaling pathway and Proteoglycans in cancer signaling pathway.ConclusionThis study preliminarily revealed the different distribution patterns of o8G modification between normal CaCO2 cells and senescent CaCO2 cells. Our study established the link between o8G modification and cancer cell senescence, which provides a new insight into the mechanism of cancer cell senescence and a potential therapeutic target for subsequent cancer treatment.